Rapid identification of mcr-1-positive Escherichia coli from patient urine using a novel lipid-based MALDI-TOF-MS assay. Issue 12 (17th December 2021) - Smith, Richard D.; Izac, Jerilyn R.; Ha, Michael; Yang, Hyojik; Johnson, J. Kristie; Ernst, Robert K.
Abstract : Mobilized colistin resistance ( mcr ) genes confer resistance to colistin, a last-resort antibiotic for multidrug-resistant Gram-negative infections. In this case report, we describe a novel lipid-based matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) diagnostic used to rapidly identify an mcr-1 -positive Escherichia coli directly from a patient with a urinary tract infection without the need for ex vivo growth.